Pembaharuan Hukum Keluarga Islam: Studi Perbandingan Hukum Keluarga di Brunei Darussalam dan Malaysia - Nur Amalia Firdaus, Seilla; Khosyiah, Siah; Rossyani, Murni (Zaaken: Journal of Civil and Business Law, 2024)
The introduction of "Muhammadan's Law Eactment" No. 1 around 1911 AD was the first step towards family law reform in Brunei Darussalam. While in Southeast Asia, the country that first made efforts to reform family law was Malaysia, with the creation of the Mohammaden Marriage Ordinance, No. V Year 1880 in the Straits countries. So that this research will further discuss the enactment and development of Islamic family law in these two countries. This research is a type of normative research or document study with a comparative approach. Primary data sources are taken from the family law laws of Brunei Darussalam and Malaysia. Secondary data sources come from books, journals, websites, and other sources. Data collection techniques using literature study and data analysis with descriptive analysis method. The results show that Brunei and Britain were once under British rule so that the application of family law was limited. However, the development of family law continues to grow to be more comprehensive. One of them, Brunei and Malaysia both apply fines and prison sanctions to people who have violated family law.